DEVELOPMENT OF SPECIAL FLEXIBILITY IN VOLLEYBALL PLAYERS - Rzhanov A.A.; Lebedinsky V.Yu.; Akhmatgatin A.A.; Yani A.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the means and methods for developing the special flexibility of volleyball players, methods for assessing it and influencing the effectiveness of the performance of a technical element: receiving the ball with two hands from below after a serve or an attacking blow from an opponent. Methods and structure of the study. In the course of the pedagogical experiment, the experimental group (EG) trained using the developed methodological tools that develop the special flexibility of volleyball players, including a set of special exercises and tools for its assessment. Methodological influences were carried out for 30 minutes during each training session. The control group (CG) was engaged in the program for the Children's and Youth Sports School. The experiment involved 62 pupils of the Sports School of the Olympic Reserve of the city of Angarsk, aged 11-14 years. The experiment lasted from September 2019 to September 2021. Results and conclusions. In the course of the study, it was found that in the CG there were no significant changes in the values of indicators characterizing the special flexibility and mobility of the joints that affect the effectiveness of the performance of game techniques, and in the EG their significant improvement was observed. In the process of conducting special testing, the results of performing a ball reception from below and the values of indicators characterizing the level of development of the SG were evaluated and compared. As a result of the study, a methodology for the development of special flexibility was developed, which includes a set of special exercises that develop this quality, as well as methods for assessing the values of special flexibility and the effectiveness of performing the technique from below, as a game technique that allows assessing the width of the amplitude of movement of the lower limbs and the spinal column.